Natural Reservoirs, An Nature-Based Solutions (NBS) Option for Water Conservation - Saroinsong, Fabiola; Timbayo, Jeane E. S. (Journal of Literacy and Education, 2025)
Nature-based solutions (NBS) represent a paradigm shift in water resources management, leveraging ecosystem functions to address hydrological challenges while delivering co-benefits for biodiversity and human well-being. The objectives of this article are: (1) to elucidate the conceptual foundations and terminology of natural reservoir as NBS water storage system; (2) to describe the benefits and  functional mechanisms; and (3) to describe the implementation of natural reservoirs utilization. This systematic literature review examines water retention infrastructure functioning as natural reservoirs within the NBS framework, including constructed wetlands, retention ponds, floodplain restoration, and beaver dam analogues. Following PRISMA guidelines, we analyzed peer-reviewed publications (2014–2024) with DOI identifiers from Scopus-indexed journals to elucidate conceptual foundations, functional mechanisms, and implementation techniques. Results demonstrate that NBS water storage systems provide multifunctional benefits: flood peak attenuation (15–30% runoff reduction), groundwater recharge enhancement, water quality improvement through biogeochemical processes, and habitat creation. European implementations dominate the literature (68% of studies), particularly in Germany, Czech Republic, and Slovakia where landscape-based water retention measures have been integrated into river basin management. Notable implementations include the Püspökszilágy NWRM project (Hungary) eliminating flash floods while stabilizing groundwater, and extensive constructed wetland networks in China treating wastewater while providing 103.3 mm soil storage capacity in urban areas. Critical success factors include site-specific hydrological assessment, native vegetation selection, and adaptive management protocols. Challenges persist regarding long-term sedimentation management, climate resilience under extreme events, and standardized monitoring frameworks. This review establishes that natural reservoir as one of NBS water storage systems, when properly designed, deliver superior ecosystem service bundles compared to conventional gray infrastructure while enhancing landscape connectivity and climate adaptation capacity.